Macromol. Mater. Eng. 2/2013. Issue 2 (8th February 2013) - Badrinarayanan, Prashanth; Rogalski, Mark; Wu, Hongchao; Wang, Xiaofeng; Yu, Wonjong; Kessler, Michael R.
<x xml:space="preserve">Abstract</x> Front Cover: The potential of an epoxy resin to tailor the coefficient of thermal expansion using unique, negative‐CTE ZrW2O8 nanoparticles while also achieving simultaneous enhancements in mechanical and electrical properties of the matrix is investigated. Improvements in thermomechanical and dynamic mechanical properties of the epoxy matrix are achieved with no detrimental effect on the dielectric strength, which suggests that these nanocomposites could be viable candidates for a wide range of electrical applications. Further details can be found in the article by Prashanth Badrinarayanan, Mark Rogalski, Hongchao Wu, Xiaofeng Wang, Wonjong Yu, and Michael R. Kessler* on page 136. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>